APPLICATION OF THE FMEA METHOD TO KNOW THE FACTORS CAUSING WELD DEFECTS IN THE BOILER FABRICATION PROCESS - Wirani, Ayu Puspa; Janwar, Muhammad; Wajdi, Muhammad Syahro (IJOSMAS, 2021)
- In an era of changing consumer needs and high demand for reliable products, companies need to improve product quality to be able to maintain their business in a competitive industrial world. Including the quality of the boiler as a component of the thermal power plant must be maintained at good performance so that the power plant can operate normally. This study aims to improve the quality of boiler fabrication through the application of the FMEA method. The results showed that the average percentage of weld defects from the results of radiographic testing exceeded the target set by the company for tube-tube, header-header and header-end caps welding joints. Types of welding defects that often occur are porosity welding defects with a percentage of 36%. Based on the data analysis, there are four main factors that influence the welding results, including the ability of the welder, the conditioning of the welding electrode, the parameters of the welding machine, and environmental conditions. Methods: This study aims to determine the factors that cause welding defects in the boiler fabrication process in a power plant component company. The type and design of the research carried out is quantitative research with case studies. From the results of data processing regarding the defect rate, the research focused on the results of radiographic testing that exceeded the company's target. The result was that the type of defect with the highest percentage was porosity of 35.8% or around 36%. That is, most of the welding defects that cause failure in the welding results are the occurrence of weld porosity. Meanwhile, for other types of welding defects, the percentage is below 30%. Based on the results of data collection and analysis, it can be concluded as follows: the dominant type of weld defect in boiler fabrication from radiographic test results is porosity weld defect, the main causes of porosity welding defects include the ability of the welder, not conditioning the electrode/welding wire, welding machine parameters, and environmental conditioning. Quality improvements include, among others, the welder by holding training and testing the WPQ (Welding Performance Qualification) again for each project, performing treatment on the welding wire, supervising the setting of the welding machine parameters, and covering the welding area with cloth or tarpaulin so that the welding area is free from wind. and other environmental conditioning.